2010
DOI: 10.1007/bf03215838
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating relaxation of high-strength bolts by parameters on slip faying surfaces of bolted connections

Abstract: The clamping force of a high-strength bolt reduces within a certain time period after the initial clamping force. When special treatments are used on a faying surface, the clamping force is relaxed severely. Tests were conducted for slip critical joints subjected to various faying surface parameters. Relaxation occurred for slip resistant joints with an uncoated surface that had been shot-blasted, cleaned, milled or rusted. It was observed that the initial clamping force dropped from 6.2% to 8.0% after 744 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…The existing research in which pretension force in high strength bolts is measured either by strain gauges glued to the bolt shank [16] or by strain gauges fitted inside the shank can be divided into those explorations in which no bolt calibration has ever been carried out [17], into explorations in which a force is additionally controlled by strain gauges in a few bolts [11] and explorations in which calibration of every bolt has been performed separately [10], [9]. Experimental research [8] performed on 126 bolts showed that the only thing that was right and acceptable was to calibrate each bolt separately given a big difference in rigidity of bolts that are of various lengths and rigidities in some parts of the bolt, all of which leads to a deviation from measured strains in the bolt compared to nominal ones.…”
Section: Eksperimentalna Kalibracija Sile Prednaprezanja U Visokovredmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing research in which pretension force in high strength bolts is measured either by strain gauges glued to the bolt shank [16] or by strain gauges fitted inside the shank can be divided into those explorations in which no bolt calibration has ever been carried out [17], into explorations in which a force is additionally controlled by strain gauges in a few bolts [11] and explorations in which calibration of every bolt has been performed separately [10], [9]. Experimental research [8] performed on 126 bolts showed that the only thing that was right and acceptable was to calibrate each bolt separately given a big difference in rigidity of bolts that are of various lengths and rigidities in some parts of the bolt, all of which leads to a deviation from measured strains in the bolt compared to nominal ones.…”
Section: Eksperimentalna Kalibracija Sile Prednaprezanja U Visokovredmentioning
confidence: 99%
“…Postojeća istraživanja u kojima se sila prednaprezanja u visokovrednim zavrtnjevima meri pomoću mernih traka zalepljenih na telo zavrtnja [16] ili ugrađenih u njega, mogu se podeliti na: istraživanja u kojima nije vršena kalibracija zavrtnjeva [17], istraživanja u kojima se na malom broju zavrtnjeva sila dodatno kontroliše pomoću mernih ćelija [11] i istraživanja u kojima je izvršena kalibracija svakog zavrtnja ponaosob [10], [9]. Eksperimentalnim istraživanjem [8] na 126 zavrtnjeva, pokazano je da je jedino ispravno i prihvatljivo vršiti kalibraciju svakog zavrtnja, s obzirom na velike razlike u krutosti zavrtnjeva različite dužine, kao i u krutosti delova zavrtnja, što dovodi do odstupanja merenih od nominalnih dilatacija zavrtnja.…”
Section: Introductionunclassified
“…Early studies [39] indicated that the average loss of preload was 5% of the maximum pretension applied to the bolts. A more recent study [40] showed that the loss of preloaded ranged from 6.2 to 8.0% depending on the faying surface treatment. Hence, to account for the relaxation of the bolt preload, the actual preloading applied to the HS bolts with the SMA ring spring system may need to be increased accordingly, and an increase of around 8% may be a reasonable value based on the research data.…”
Section: Self-centring Beam-to-column Connectionsmentioning
confidence: 98%